PENGARUH PROPORSI CAMPURAN BATU APUNG TERHADAP KUAT TEKAN BATAKO RINGAN - Santi Wulandari; Bq Rina Amalia; Bq Azmi Sukroyanti (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
This study discusses the use of pumice as an aggregate material to reduce sand in making light brick. The purpose of this study was to, 1) find out the compressive strength of the brick by using a mixture of pumice stone, 2) knowing the exact number of comparisons between sand, cement and pumice to produce a lightweight brick. The research stage was carried out through several stages, namely: 1) Preparation of materials, 2) Making of brick making, on sample A1 (pumice stone 0.50 cm in diameter) with composition (20% SM + 50% PS + 30% BA), A2 (20% SM + 40% PS + 40% BA), A3 (20% SM + 30% PS + 50% BA) while in samples B1, B2, B3 (pumice stone 0.25 cm in diameter) and C1, C2, C3 (rock smoothed float) equal to sample A1, A2, A3. 3) Light brick drying process is carried out for 22 days, 4) density test and compressive strength, 5) data analysis. A lightweight brick made of cubes with a side length of 9 cm (volume 729 cm3). The results showed that the density of the samples A1, A2, A3 in the composition as above were: 1.87 kg / m3, 1.48 kg / m3, 1.73 kg / m3. While the density of samples B1, B2, B3 and C1, C2, C3 as above composition are: 1.43 kg / m3, 1.64 kg / m3, 1.69 kg / m3 and 1.92 kg / m3, 1, 69 kg / m3, 1.57 kg / m3. The best density in sample B1 with a composition of 20% SM + 50% PS + 30% BA = 1.43 kg / m3. The compressive strength values in a row, such as the composition above, are: sample A = 4.66 MPa, 3.97 MPa, 8.29 MPa. Samples B = 5.12 MPa, 6.73 MPa, 6.48 MPa. Samples C = 8.1 MPa, 4.77 MPa, 6.65 MPa. The best compressive strength value on A3 sample with a composition of 20% SM + 30% PS + 50% BA = 8.29 MPa. This study proves that pumice can be used in the manufacture of lightweight concrete blocks that have low density values and high compressive strength.